An applied logistic model for online purchase decision via web-building experiments. (4th December 2009) - Yeh, Robert; Yan, Ruiliang
A commercial website was built to test six factors in consumers' online purchase decisions. A data set of 128 observations using the designed commercial website was collected to build a multiple-logistic, binary-purchase decision model. The individual and collective impacts of the selected six factors were tested and later quantified. The main contribution of this study was to combine the six proven factors and show their quantified influence over a designed commercial website. As many researchers have pointed out, although some factors do seem to have obvious direct impacts, their joint quantified impact requires a modelling procedure such as our multiple-logistic model to reveal their quantitative relationships. We believe that, with the comparative quantified impact of these factors, e-commerce companies can have better access to the evaluation of their return on investment on website features.